2018
DOI: 10.1155/2018/3897478
|View full text |Cite
|
Sign up to set email alerts
|

Combined Rosiglitazone and Forskolin Have Neuroprotective Effects in SD Rats after Spinal Cord Injury

Abstract: The peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist rosiglitazone inhibits NF-κB expression and endogenous neural stem cell differentiation into neurons and reduces the inflammatory cascade after spinal cord injury (SCI). The aim of this study was to explore the mechanisms underlying rosiglitazone-mediated neuroprotective effects and regulation of the balance between the inflammatory cascade and generation of endogenous spinal cord neurons by using a spinal cord-derived neural stem cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We have previously reported that the PPAR- γ ligand, rosiglitazone, promotes functional recovery after SCI by blocking the loss of local neurons and decreasing NF- κ B expression [18, 19]. Loss of local neurons from SCI is largely induced by persistent inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the PPAR- γ ligand, rosiglitazone, promotes functional recovery after SCI by blocking the loss of local neurons and decreasing NF- κ B expression [18, 19]. Loss of local neurons from SCI is largely induced by persistent inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The drug binds to the peroxisome proliferator-activated receptors in adipocytes and renders the cells more responsive to insulin. The neuroprotective effect of Rosiglitazone and other thiazolidinediones has been studied extensively and a beneficial effect has been suggested through inhibition of inflammatory responses, pro-apoptotic cascades, and mitochondrial metamorphosis [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone is a clinical drug for type 2 diabetes that exhibits the potential to inhibit the inflammatory response [ 19 ]. It has been reported that rosiglitazone has a positive effect in reducing intestinal inflammation in various experimental models [ 20 ].…”
Section: Discussionmentioning
confidence: 99%